Organ transplant and Covid‐19 vaccination: Considering the ethics of denying transplant to unvaccinated patients. Issue 5 (20th January 2022) - Hurst, Daniel J.; Potter, Jordan; Padilla, Luz A.
Abstract: Recently, a number of organ transplant centers in the United States have proposed to only allow patients who have received the Covid‐19 vaccination to be active on their transplant waiting list. This raises numerous ethical issues. This analysis utilizes current empirical data and the guidelines on the ethics of organ allocation published by the Organ Procurement and Transplant Network to guide our ethical reasoning. We conclude that it would be permissible to mandate Covid‐19 vaccination as a condition of being listed for an organ transplant at a transplant center and offer recommendations for how to do so.